2018
DOI: 10.1073/pnas.1718646115
|View full text |Cite
|
Sign up to set email alerts
|

Division-independent differentiation mandates proliferative competition among stem cells

Abstract: Cancer-initiating gatekeeper mutations that arise in stem cells would be especially potent if they stabilize and expand an affected stem cell lineage. It is therefore important to understand how different stem cell organization strategies promote or prevent variant stem cell amplification in response to different types of mutation, including those that activate proliferation. Stem cell numbers can be maintained constant while producing differentiated products through individually asymmetrical division outcomes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(74 citation statements)
references
References 55 publications
6
68
0
Order By: Relevance
“…If each stem cell repeatedly divides to produce a stem cell and a differentiated product (‘invariant single-cell asymmetry’), the rate of division must simply be matched to the required supply of product cells. More commonly, however, a group of stem cells in a given location is maintained by ‘population asymmetry’, where individual stem cells exhibit non-uniform, stochastic behaviors and differentiation is commonly not temporally or mechanistically linked to division of the same stem cell ( Reilein et al, 2018 ; Ritsma et al, 2014 ; Rompolas et al, 2016 ; Simons and Clevers, 2011 ). The behavior of such stem cells is likely guided substantially by extracellular signals and it is commonly presumed that regulation is achieved substantially by defining a compartment with fixed dimensions that can maintain stem cells.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…If each stem cell repeatedly divides to produce a stem cell and a differentiated product (‘invariant single-cell asymmetry’), the rate of division must simply be matched to the required supply of product cells. More commonly, however, a group of stem cells in a given location is maintained by ‘population asymmetry’, where individual stem cells exhibit non-uniform, stochastic behaviors and differentiation is commonly not temporally or mechanistically linked to division of the same stem cell ( Reilein et al, 2018 ; Ritsma et al, 2014 ; Rompolas et al, 2016 ; Simons and Clevers, 2011 ). The behavior of such stem cells is likely guided substantially by extracellular signals and it is commonly presumed that regulation is achieved substantially by defining a compartment with fixed dimensions that can maintain stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…The consequent deductions of FSC number, location and behavior were largely re-stated as dogma over the following two decades despite some contrary observations ( Hartman et al, 2015 ; Nystul and Spradling, 2007 ; Nystul and Spradling, 2010 ; Zhang and Kalderon, 2001 ). A comprehensive re-evaluation, which included the analysis of all FSC lineages, without any prior assumptions about their behavior, showed that individual FSCs were frequently lost or duplicated ( Reilein et al, 2017 ) and that FSC differentiation to an FC was not temporally coupled to, or dependent upon division of the same FSC ( Reilein et al, 2018 ). These characteristics of maintenance by population asymmetry, together with independent cell division and cell differentiation events and decisions, are shared by two very important and intensively studied types of mammalian epithelial stem cell, in the gut and in the epidermis ( Jones, 2010 ; Mesa et al, 2018 ; Ritsma et al, 2014 ; Rompolas et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations